Opinions of Investors on Nepal Stock Exchange Limited (NEPSE) Online Trading System - Vaidya, Rashesh (Prithvi Academic Journal, 2021)
Nepal Stock Exchange Limited (NEPSE) is only a secondary market in Nepal. After almost three decades of its establishment, the NEPSE trading system turned fully automated on January 17, 2021. The new system is named NEPSE Online Trading System (NOTS), which was launched on November 6, 2018. After the breakout of the COVID-19, the NOTS users using NEPSE online Trade Management System (TMS) and Uniform Resource Locator (URL) increased due to the nation-wide lockdown as well as the compulsion from the governing body. Hence, the paper attempts to get opinions from the NOTS users about its features and performance. The paper has taken 300 NOTS users as samples for the survey purpose. The online survey was conducted for the study. A 5–points Likert scale-based questionnaire was forwarded to the potential online traders (investors) through an online platform such as messenger and email. The study has followed descriptive statistics and a one-sample t-test to interpret the collected data from the NOTS users. The study found that there is an issue of the market data display in the NOTS platform, which needs to be addressed as soon as possible. At the same time, the respondents stated that the best parts of NOTS were that it has helped them to specify and customize the securities, price, and volume that one would like to trade on a real-time basis.